Educational approaches beyond digital capitalism - English English (Seminar.net)
This article focuses on the question of how young people in different educational settings can be methodically and didactically motivated to deal with digital capitalism. To this end, theoretical perspectives on digital capitalism, the positionality of (capitalism-)critical (political media) education and its seemingly apparent self-evidence are problematised in the first step. Next, “Critical Data Literacies – a practice-based research project on digital capitalism” is outlined. Its aim was to develop educational methods for interrogating different aspects of digital capitalism by fostering critical-aesthetic data literacies. The proposed methods have been tested with youth, students and educational professionals in Germany. Empirical results from the accompanying qualitative research are presented here to generate perspectives for comparable project contexts and deepening research.